PERBANDINGAN KINERJA USAHA DALAM SISTEM PEMASARAN ONLINE DAN OFFLINE PADA KOMODITAS SAYURAN ORGANIK - Gordianus Jana; Asnah Asnah; Dyanasari Dyanasari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the comparison of marketing performance with different marketing systems (online and offline) on organic vegetable commodities in the Sri Anom Mulyo farmer group 04 Glonggong, Temas Village, Batu City and analyze the impact of online marketing on business performance on organic vegetable commodities in the Sri Anom farmer group. Mulyo 04 Glonggong, Temas Village, Batu City. This research was conducted on the Sri Anom Mulyo farmer group 04 Glonggong, Temas Village, Batu City, the research time will start in October 2021 until December 2021. The data analysis technique used in this study is a quantitative descriptive method to explain the opinion of the farmer group before and after implementing digital marketing, Revenue (Q), Profit (π), Revenue to cost ratio (R/C), Break Event Point (BEP), comparative analysis (comparison) and partial test (t-test). The results of the study concluded that the results of the sixn (6) organic vegetable commodity cultivated by farmers in the Sri Anom Mulyo 04 Glonggong farmer group with the paired sample t-test t test method showed that there was a significant difference in business performance with online and offline marketing systems in 2019, 2020, and 2021. Commodities pakchoy, green andewi, carrots, broccoli, romaine lettuce and caisim show differences in business performance with online and offline marketing systems from 2019 to 2021 with a sig value for each commodity less than 0.05 (0.000 < 0.05). These results can be concluded that H1 is accepted and H0 is rejected. Commodities marketed online have an impact on performance, this can be seen in the small quantity of commodities marketed but can offset the performance of businesses marketed offline.